Different Treatment Protocols of Retained Fetal Membranes and its Effect on Serum Profile, Uterine Involution and Postpartum Fertility in Cows - Shah, AI; Patel, DM; Sarvaiya, NP; Madhira, SP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This study was undertaken on 36 freshly calved cows randomly divided into 6 equal groups under field conditions. Cows of group-VI that shed placenta within 8-12 hours postpartum naturally served as healthy control. The cows with retained fetal membranes (RFM, n = 18) for more than 12 hrs were managed either by manual removal of placenta without antibiotics (group-I), parenteral antibiotic (Ceftiofur 1 g i/m) for three consecutive days (group-II) or a combination of both (group-III). In group-IV and group-V, cows were administered with Inj. Oxytocin @ 50 IU i/m and Inj. Dinoprost tromethamine (PGF2α) @ 25 mg i/m, respectively, immediately after parturition and time of placental shedding was recorded. The overall prevalence of Brucellosis by RBPT was found to be 5.55 % amongst these 36 animals. The placental expulsion in groups following medicinal treatment was found to be 50 (3/6) % in Ceftiofur alone by 3 days (group-II), and 66.67 (4/6) % in Oxytocin (group-IV) and 100 (6/6) % in PGF2α inj. (group-V) groups within 12 hrs. The time of uterine involution in groups I to VI was found to be 42.00 ± 1.94, 39.50 ± 0.99, 40.67 ± 1.39, 38.33 ± 1.55, 37.50 ± 1.02 and 37.33 ± 1.76 days, respectively, while the interval for the appearance of first postpartum estrus was 54.83 ± 2.06, 51.00 ± 1.05, 52.17 ± 1.96, 50.17 ± 2.03, 48.67 ± 1.90 and 49.17 ± 1.55 days, respectively, which did not vary statistically. The mean serum progesterone profile obtained on day 0 and day 21 postpartum was statistically non-significant between groups. However, it was significantly (p <0.05) lower on day 0 as compared to day 21 in group-I, II and VI. The levels on day 0 coincided with the time of blood sampling after calving. The high level of serum P4 on day 0 in group-IV and V could be due to sampling immediately after calving. The serum calcium and phosphorus levels were significantly (p <0.05) lower on day 0 than on day 21, but not the magnesium. The group effect was however non-significant for any of three minerals. It was observed that manual removal of RFM without parenteral antibiotics, resulted in puerperal metritis, cervicitis, pyometra which ultimately resulted into delayed uterine involution, delayed first postpartum estrus and thus, reduced the postpartum reproductive efficiency. It was inferred that the PGF2α and Oxytocin injections could be used as a treatment of choice for prevention of RFMs in cattle.